1997
DOI: 10.1523/jneurosci.17-23-09353.1997
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Contextual Fear after Lesions of the Hippocampus: A Disruption of Freezing But Not Fear-Potentiated Startle

Abstract: The roles of the dorsal hippocampus and the central nucleus of the amygdala in the expression of contextual fear were assessed using two measures of conditioned fear: freezing and fear-potentiated startle. A discriminable context conditioning paradigm was developed that demonstrated both conditioned freezing and fear-potentiated startle in a context paired previously with foot shock, relative to a context in which foot shock had never been presented. Post-training lesions of the central nucleus of the amygdala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
154
2
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(177 citation statements)
references
References 45 publications
18
154
2
3
Order By: Relevance
“…The difference between this value and the baseline motor activity (measured during the habituation period, see above) was used as a measure of "freezing." Preliminary studies in this laboratory as well as in other laboratories (Leaton and Borszcz, 1985;McNish et al, 1997) showed that this kind of measure is highly correlated with freezing quantified by an observer.…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…The difference between this value and the baseline motor activity (measured during the habituation period, see above) was used as a measure of "freezing." Preliminary studies in this laboratory as well as in other laboratories (Leaton and Borszcz, 1985;McNish et al, 1997) showed that this kind of measure is highly correlated with freezing quantified by an observer.…”
Section: Methodsmentioning
confidence: 58%
“…It should be noted that freezing was not directly observed, but attenuation of motor activity in the startle test chamber was measured, which is highly correlated with freezing (Leaton and Borszcz, 1985;McNish et al, 1997). The question now is why the studies of Davis and colleagues (Miserendino et al, 1990;Campeau et al, 1992;) revealed contradictory results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although there is a lack of support for the hyperactivity account of contextual freezing deficits, McNish et al (1997) presented data showing that context-potentiated startle was not affected by DH lesions made immediately after training. This suggests that the deficits in contextual fear we have observed may be specific to the freezing response.…”
Section: Performance Account Of Contextual Freezing Deficits After Himentioning
confidence: 91%
“…Not all studies find that lesions of the hippocampus affect context conditioning (Frankland et al 1998;McNish et al 1997;Winocur 1997). Recent preclinical evidence indicates that context conditioning is hippocampus-dependent for complex but not simple environments (Moses et al 2007).…”
Section: Context Conditioningmentioning
confidence: 99%